PENGARUH MODEL PEMBELAJARAN TANDUR TERHADAP AKTIVITAS DAN HASIL BELAJAR PADA MATERI VIRUS SISWA KELAS X SMA NEGERI 2 SKANTO KABUPATEN KEEROM - Siti Daryati (Program Magister Pendidikan IPA, Program Pascasarjana Universitas Cenderawasih, 2018)
Abstrack The data analysis using SPSS version 21. Results of regression model of learningTANDUR (X) on learning activities (Y1) with the equation Y1 = 12,977 + 1,662X, the effect of 77.2% and a learning model TANDUR (X) on learning outcomes (Y2 ) with the equation Y2 = -13,399 + 2,283X, the impact of 90,6%. The results of correlation analysis TANDUR learning model (X) on learning activities (Y1) of 0,850 and a learning model TANDUR (X) on learning outcomes (Y2) amounted to 0,952, this means learning model TANDUR effect on activity and learning outcomes.Research results to direct that: (1) there are significant learning model TANDUR on learning activities amounted to 77,2%, (2) there are significant learning model TANDUR the learning outcomes of 90,6%, and (3) there is an increase learning outcomes with value n- average gain of 0,63 learning outcomes with the medium category.Keywords: Learning Model TANDUR, Activities, Learning Outcomes, Virus.